Comparative study of conventional Pap smear and liquid based cytology as a screening method for cervical cancer - Atla, Bhagyalakshmi; Prasad, Uma; Botta, Venkata Satya Kartheek; Namballa, Uma; Pujari, Lahari; Lalam, Neelima (International Journal of Research in Medical Sciences, 2021)
Background: Pap smear is the conventional screening procedure for cervical cancer. Liquid based cytology has been developed as a cost effective alternative as it has a short screening time, better morphology and clean background while also providing residual material to test for HPV DNA. Therefore this study is undertaken to know the role of Liquid-based cytology in evaluating pre-malignant and malignant lesions of cervix. Objectives of current study were to study the distribution of various cervical lesions on liquid-based cytology and compare them with conventional Pap smears. To know the role of liquid-based cytology in evaluating pre-malignant and malignant lesions of cervix Methods: This study included 200 women attending to gynaecology OPD and the samples were taken for both conventional cytology and liquid based cytology. The smears were studied in detail and were interpreted as per The Bethesda system 2014 of reporting pap smears and results are recorded and compared. Results: The commonest cervical lesions on pap smears by liquid-based cytology are NILM-reactive changes (N=92, 46%), NILM Candida infection is seen in 9 cases (4.5%) and trichomonas vaginalis infection in 5 cases (2.5%). Unsatisfactory smears on LBC is less when compared to conventional smears as the coefficient of correlation is significant with p value of 0.000422 (<0.05). The number of cases with a diagnosis of ASCUS is reported more in liquid-based cytology (9 cases) when compared to conventional Pap (8 cases). The number of cases with diagnosis of HSIL, SCC is reported more in liquid based cytology (7 cases) when compared to conventional Pap (4 cases). Epithelial cell abnormality were easily diagnosed on LBC smears with significant p value of 0.002414 (<0.05). Conclusions: Liquid-based cytology has advantages of fewer unsatisfactory smears and better detection of epithelial cell abnormalities when compared to conventional Pap smears. LBC is better for the screening of premalignant and malignant lesions of cervix even though it is costly.